Rail Transport-Systems Approach - Sładkowski, Aleksander; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book shows how the systems approach is employed by scientists in various countries to solve specific problems concerning railway transport. In particular, the book describes the experiences of scientists from Romania, Germany, the Czech Republic, the UK, Russia, Ukraine, Lithuania and Poland. For many of these countries there is a problem with the historical differences between the railways. In particular, there are railways with different rail gauges, with different signaling and communication systems, with different energy supplies and, finally, with different political systems, which are reflected in the different approaches to the management of railway economies. The book's content is divided into two main parts, the first of which provides a systematic analysis of individual means of providing and maintaining rail transport. In turn, the second part addresses infrastructure and management development, with particular attention to security issues. Though primarily written for professionals involved in various problems concerning railway transport, the book will also benefit manufacturers, railway technical staff, managers, and students with transport specialties, as well as a wide range of readers interested in learning more about the current state of transport in different countries.
Part I: Means of Transport and Maintenance -- Effects of Braking Characteristics on Longitudinal Dynamics of Short Pas-senger Trains -- The Behavior of Traction Power Supply System of AC 25 kV During Operation -- Systems Approach to the Analysis of Electromechanical Processes in Asynchronous Traction Drive of Electric Locomotive -- The Aspects of Modernization of Diesel-Electric Locomotives and Platform for Transportation of Railway Switches in the Lithuanian Railways -- Systems Approach to Organization of Locomotive Maintenance on Ukraine Railways -- Part II: Infrastructure and Management in Railway Transport -- Systematic and Customer Driven Approach on Cost Efficient Improving Interlocking and Signaling in Train Transport -- Train Protection Systems in Different Railway Gauges -- Modelling of Traffic Smoothness for Railway Track Closures in the Rail Network -- Assessment of Polish Railway Infrastructure and the Use of Artificial Intelligence Methods for Prediction of its Further Development.-Dynamic Optimization of Railcar Traffic Volumes at Railway Nodes.
Keywords: Transportation engineering; Traffic engineering; Computational intelligence; Business logistics; Transportation Technology and Traffic Engineering; Computational Intelligence; Logistics